ANALOG SEISMIC RECORDING REVISITED - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 1993)
Analog single channel seismic recording is a conventional technique commonly used in subsurface profiling. One of its advantage is the resolution much higher than that of digital seismic recording. This advantage can be very useful in interpreting detail stratigraphic and structural subsurface features of the digital seismic section. In this case both profile are complementary.